Active site voltage clamp fluorometry of the sodium glucose cotransporter hSGLT1 - Gorraitz, Edurne (Proc Natl Acad Sci U S A, 2017)
In the human sodium glucose cotransporter (hSGLT1) cycle, the protein undergoes conformational changes where the sugar-binding site alternatively faces the external and internal surfaces. Functional site-directed fluorometry was used to probe the conformational changes at the sugar-binding site. Residues (Y290, T287, H83, and N78) were mutated to cysteines. The mutants were expressed in Xenopus laevis oocytes and tagged with environmentally sensitive fluorescent rhodamines [e.g., tetramethylrhodamine (TMR)-thiols]. The fluorescence intensity was recorded as the mutants were driven into different conformations using voltage jumps. Sugar binding and transport by the fluorophore-tagged mutants were blocked, but Na(+) binding and the voltage-dependent conformational transitions were unaffected. Structural models indicated that external Na(+) binding opened a large aqueous vestibule (600 Å(3)) leading to the sugar-binding site. The fluorescence of TMR covalently linked to Y290C, T287C, and H83C decreased as the mutant proteins were driven from the inward to the outward open Na(+)-bound conformation. The time courses of fluorescence changes (milliseconds) were close to the SGLT1 capacitive charge movements. The quench in rhodamine fluorescence indicated that the environment of the chromophores became more polar with opening of the external gates as the protein transitioned from the inward to outward facing state. Structural analyses showed an increase in polar side chains and a decrease in hydrophobic side chains lining the vestibule, and this was reflected in solvation of the chromophore. The results demonstrate the opening and closing of external gates in real time, with the accompanying changes of polarity of the sugar vestibule.